MANAJEMEN ALOKASI DANA DESA (ADD) TAHUN 2013 DI DESA MEKAR SARI KECAMATAN MERBAU KABUPATEN KEPULAUAN MERANTI - Afandi, Zulham; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Village Fund Allocation Management (ADD) In 2013 the village of the District Mekarsari Merbau Meranti Islands District. Village Fund Allocation (ADD) is a fund allocated by the Government of the District to the village, which is sourced from the financial balance of central and local received by the District. Village Allocation Fund is a fund that is significant enough for the village to support the programs of the village. Good financial management of the budget until the realization of the need to involve community leaders and government officials Desa.Salah the government's strategy to help the country become self-sufficient and autonomous by giving the Village Fund Allocation (ADD). Use of funds ADD is 30% for operational costs and the Village Government Village Consultative Body (BPD). 70% for community empowerment and capacity building of Village Government.The aim of the study is to examine the management fund allocation Village (ADD ) in 2013 Mekar Sari subdistrict Merbau District archipelago Meranti and also as well as to determine the inhibiting factors in the management of the Village Fund Allocation (ADD ) In 2013 the Village bloom Sari subdistrict Merbau District archipelago meranti.The method used is descriptive research with a qualitative approach in data collection , researchers use interviewing techniques , observation , documentation and studies kepustakaan.Dengan use informants as sources of information and data analysis techniques by means of data collection , data presentation , redukasi data and draw conclusions.The results showed that the Management of the Village Fund Allocation (ADD ) Mekar Sari is not optimal and not targeted for their intended purpose , a portion of the funds the Village Fund Allocation (ADD ) for community empowerment is used for operational costs village government and BPD so that the use of the Village Fund Allocation ( ADD) is not as intended. Management must have a good budget planning, organizing clear , the exercise of good , effective supervision and peggerakan / right direction . Inhibiting factors in the management of the Village Fund Allocation (ADD ) Mekar Sari village is a human resources ( HR) , Motivation and attitude / behavior.Keywords : Management , Village Fund Allocation (ADD )